THE INFLUENCE OF COMMUNICATION STRATEGIES AND EDUCATIONAL PROGRAMS ON COMMUNITY PARTICIPATION AT LAZNAS YATIM MANDIRI MAKASSAR - Hidir, Amrullah; Hasbiah, Siti; Ruma, Zainal; Burhanuddin; Aswar, Nurul Fadilah; Muhammad, A Fadel (Malaqbi Publisher, 2023)
There are many factors that become obstacles for zakat institutions in their development, one of these factors is the lack of public understanding of the concept of zakat, the evaluation of strategies that are not optimal and the effectiveness of the program, so that communication strategies and educational programs are needed which will generate knowledge related to the institution to increase community participation. This research is an explanatory quantitative study that aims to analyze the factors that influence how community participation in LAZNAS Yatim Mandiri Makassar City, using a population of people who have lived and had direct contact with LAZNAS Yatim Mandiri Makassar City, with a sample size of 96 respondents. The data used was obtained by distributing questionnaires via google form. The results of this study indicate that the communication strategy partially has no significant effect on community participation with a significant value of 0.258> 0.05 and the education program has a positive and significant effect with a value of 0.000 <0.05 on community participation. This shows the importance of improving educational programs to increase public understanding of the concept of zakat and the activities of zakat institutions, this can be a reference for other zakat institutions in increasing community participation and the effectiveness of the programs carried out.